Loss and Gorgeous (A Pastoral Study on Grace Counseling) - Genoveva Leasiwal (Eduvest - Journal of Universal Studies, 2022)
This journal aims to analyze the role of mentoring and grief counseling due to the loss or death of someone who cannot be forgotten and resolved so that it becomes a heavy burden, and sucks out one's creativity. The longer the healing process, the greater the risk of grief for its integrity. In this case, people grieving because of death need to get attention from various parties, one of which is the Church in the form of an assistance, for this reason this study aims to describe and analyze forms of pastoral care that has been carried out so far and to develop a pattern of pastoral assistance for people grieving due to death. To obtain data, the authors use direct interview techniques with informants consisting of servants and people who experience grief due to death, both unexpected and sudden deaths. The results obtained from this study indicate that the pastoral care that has been carried out by the ministry is only temporary and is carried out when a grieving person contacts the minister, so that the grieving person is still in an atmosphere of grief because he does not receive effective assistance. The pastoral assistance that is carried out requires a pattern that can serve as a guide for ministers in providing help, for that the author offers a pattern of assistance that can be adapted to the needs of grieving people with different types of grief, namely a spiral mentoring pattern where the counselee will not always be the counselee because when he has been helped he will empower himself to become a counselor and can help others too